Development of Innovative Learning Media for Number Recognition Using "Mama Langka" in Early Childhood - Elina Intan Apriliani; Iffah Mukhlisah; Anita Wardani; Annafi’ Nurul ‘Ilmi Azizah; Praptiningsih Praptiningsih (Journal of Childhood Development, 2024)
This study aims to develop innovative learning media through the introduction of numbers with "Mama Rare" lamp media in early childhood. In the process of learning activities, learning media greatly determines the success in mastering the material provided. One of the most important factors in developing early childhood learning media is designing learning media to be interactive and attract children's attention and encourage children to be actively involved in the learning process. This research was conducted using the R&D(Research and Development) approach. In the initial development process, researchers consulted with media experts, material experts and field experts (Early Childhood Education). The next stage was an initial trial with a sample of 20 students, followed by a final trial on 30 students and analyzed with the t test. The results showed that: 1) In the needs analysis found the need for innovative learning media Mama Langka to introduce numbers in early childhood, 2) Learning Media that is suitable for use as a means of teacher learning media is made by considering an attractive appearance so as to make learning media easier to understand, not boring, and easy to carry everywhere. 3) Mama Langka Innovative Learning Media is effectively used to introduce numbers in early childhood. This can be seen from the significance value obtained is 0.000 <0.05. The t test in the initial trial that the tcount is 12,010> t table 1.725 and the final stage of the tcount is 17,218> t table 1.725, which means that based on the pretest and posttest that has been done to 30 children at PAUD RA Chairunnisa Sukoharjo, there is a difference in the ability to recognize numbers before and after using innovative learning media "Mama Langka".